Universal availability of publications (UAP) : a programme to improve the national and international provision and supply of publications - Line, Maurice Bernard; Vickers, Stephen (München ; New York : Saur, 1983)
This book is to introduce the concept of universal availability of publication, to describe it's various components.
Includes bibliographical references (p. 117-130).
oo 22/01/2019
Loans
Keywords: Collection development (Libraries); Library cooperation; Universal bibliography; Interlibrary loans; International librarianship